Transplantation of Neural Progenitor Cells Differentiated from Adipose Tissue-Derived Stem Cells for Treatment of Sciatic Nerve Injury. Issue 2 (June 2016) - Dong, Shasha; Liu, Na; Hu, Yang; Zhang, Ping; Pan, Chao; Zhang, Youping; Tang, Yingxin; Tang, Zhouping
Objectives: Currently, the clinical repair of sciatic nerve injury remains difficult. Previous studies have confirmed that transplantation of adipose tissue-derived stem cells promotes nerve regeneration and restoration at peripheral nerve injury sites. Methods: In this study, adipose tissue-derived stem cells were induced to differentiate into neural progenitor cells, transfected with a green fluorescent protein-containing lentivirus, and then transplanted into the lesions of rats with sciatic nerve compression injury. Results: Fluorescence microscopy revealed that the transplanted cells survived, migrated, and differentiated in rats. At two weeks post-operation, a large number of transplanted cells had migrated to the injured lesions; at six weeks post-operation, transplanted cells were visible around the injured nerve and several cells were observed to express a Schwann cell marker. Sciatic function index and electrophysiological outcomes of the transplantation group were better than those of the control group. Cell transplantation promoted the recovery of motor nerve conduction velocity and compound muscle action potential amplitude, and reduced gastrocnemius muscle atrophy. Conclusions: Our experimental findings indicate that neural progenitor cells, differentiated from adipose tissue-derived stem cells, are potential seed stem cells that can be transplanted into lesions to treat sciatic nerve injury. This provides a theoretical basis for their use in clinical applications.